Dental Health Education Using PowerPoint Media to Improve Maternal Behavior in Maintaining Dental and Oral Hygiene of Students of GMIT Baumata Elementary School - Agusthinus Wali; Melkisedek O. Nubatonis; Emma Krisyudhanti; Ratih Variani (Poltekkes Kemenkes Kupang, 2024)
Dental health education is a planned and directed effort to create an environment that encourages individuals or community groups to change their old behaviors, which are less favorable for their dental health, to behaviors that are beneficial for their dental health. Behavior change can occur naturally, influenced by the environment, or intentionally and systematically through knowledge, attitudes, and skills. The aim of this study is to determine the effect of dental health education using PowerPoint media to improve the behavior of mothers in maintaining the dental and oral hygiene of GMIT Baumata Elementary School students. This type of research is a quasi-experimental design with a pre-test and post-test research design. The population of this study includes mothers and students of GMIT Elementary School, and the research sample is the total population of mothers and students in grades I-VI at GMIT Baumata Elementary School, Taebenu District, Kupang Regency, totaling 89 people. The instruments in this study were questionnaires and dental and oral hygiene examination forms. The results of the effectiveness test analysis showed that the behavior of mothers in maintaining dental and oral health (p=0.000) significantly improved, indicating an increase in the mothers' behavior in maintaining dental and oral health. Similarly, the dental and oral hygiene status of the students (p=0.000) improved, indicating an increase in the students' dental and oral hygiene status. Therefore, it can be concluded that PowerPoint media is effective in improving the behavior of mothers in maintaining their children's dental and oral hygiene and in enhancing the dental and oral hygiene status of GMIT Baumata Elementary School students in Taebenu District, Kupang Regency. It is recommended that further research be conducted to provide comparative data.